2020
DOI: 10.20944/preprints202010.0151.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Numerical Investigation of the Collapse of the Steel Truss Roof and a Probable Reason of Failure

Abstract: This study investigates the failure of a roof with steel truss construction of a factory building in Tekirdag in North-western part of Turkey. The failure occurred under hefty weather conditions including thunderbolt, lightning strikes, heavy rain and fierce winds. In order to interpret the reason for the failure, the effects of different combinations of factors on the design and dimensioning of the roof are checked. Therefore, finite element analysis is performed several times under different assumptions and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…ChatGPT has been described as a “turning point for artificial intelligence” due to its convincing language capabilities that can produce text in response to open-ended questions that are comparable to good high school essays . Where an Internet search engine would provide a list of Internet links, ChatGPT can produce information in simple sentences and explain concepts in ways people can easily understand .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ChatGPT has been described as a “turning point for artificial intelligence” due to its convincing language capabilities that can produce text in response to open-ended questions that are comparable to good high school essays . Where an Internet search engine would provide a list of Internet links, ChatGPT can produce information in simple sentences and explain concepts in ways people can easily understand .…”
Section: Introductionmentioning
confidence: 99%
“…In the opinion piece “What Would Plato Say About ChatGPT?” Tufecki proposes that high schools and colleges are places where ChatGPT’s “most interesting and troubling aspects will become clear” . For some topics the author found ChatGPT’s responses to be cogent, well-reasoned, and clear, and because the system is interactive follow-up requests could lead to more details or changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and serpentine ((Mg,Fe)3Si2O5(OH)4) (AKKURT et al 2012;OUDA, 2015;JÓŹWIAK-NIEDŹWIEDZKA et al 2015;TUFEKCI;GOKCE, 2018). Therefore, the authors concluded that polymer concrete containing 20%…”
Section: Proposal By Khalaf Ban and Ramli (2019)mentioning
confidence: 99%